A Four-Channel DWDM Tunable Add/Drop Demultiplexer Based on Silicon Waveguide Bragg Gratings - Debin Mu; Huiye Qiu; Jianfei Jiang; Xiaofei Wang; Zhilei Fu; Yuehai Wang; Xiaoqing Jiang; Hui Yu; Jianyi Yang (IEEE Photonics Journal, 2019)
We demonstrate a thermally tunable four-channel add/drop demultiplexer based on silicon grating-assisted contra-directional couplers (contra-DCs) for 200 GHz dense wavelength division multiplexing (DWDM) systems. In order to obtain the narrow bandwidth and the rapid roll-off necessary for the DWDM, every wavelength channel is filtered dually by two identical contra-DCs cascaded in parallel. In addition, the phase apodization technique is utilized to suppress sidelobes. With these special designs, passbands of the four drop ports exhibit 3 and 20 dB bandwidths of 0.4 and 0.8 nm, respectively, while isolation between adjacent channels is better than 20 dB. Insertion losses at through and drop ports are 0.6 and ∼2.6 dB, respectively. The maximal wavelength-tunable range is up to 25 nm.